Evidence From Human Placenta, Endoplasmic Reticulum–Stressed Trophoblasts, and Transgenic Mice Links Transthyretin Proteinopathy to Preeclampsia. Issue 8 (24th May 2022) - Cheng, Shibin; Huang, Zheping; Banerjee, Sayani; Jash, Sukanta; Buxbaum, Joel N.; Sharma, Surendra
Abstract : Background: We have demonstrated that protein aggregation plays a pivotal role in the pathophysiology of preeclampsia and identified several aggregated proteins in the circulation of preeclampsia patients, the most prominent of which is the serum protein TTR (transthyretin). However, the mechanisms that underlie protein aggregation remain poorly addressed. Methods: We examined TTR aggregates in hypoxia/reoxygenation-exposed primary human trophoblasts (PHTs) and the preeclampsia placenta using complementary approaches, including a novel protein aggregate detection assay. Mechanistic analysis was performed in hypoxia/reoxygenation-exposed PHTs and Ttr transgenic mice overexpressing transgene-encoded wild-type human TTR or Ttr −/− mice. High-resolution ultrasound analysis was used to measure placental blood flow in pregnant mice. Results: TTR aggregation was inducible in PHTs and the TCL-1 trophoblast cell line by endoplasmic reticulum stress inducers or autophagy-lysosomal disruptors. PHTs exposed to hypoxia/reoxygenation showed increased intracellular BiP (binding immunoglobulin protein), phosphorylated IRE1α (inositol-requiring enzyme-1α), PDI (protein disulfide isomerase), and Ero-1, all markers of the unfolded protein response, and the apoptosis mediator caspase-3. Blockade of IRE1α inhibited hypoxia/reoxygenation-induced upregulation of Ero-1 in PHTs. Excessive unfolded protein response activation was observed in the early-onset preeclampsia placenta. Importantly, pregnant human TTR mice displayed aggregated TTR in the junctional zone of the placenta and severe preeclampsia-like features. High-resolution ultrasound analysis revealed low blood flow in uterine and umbilical arteries in human TTR mice compared with control mice. However, Ttr −/− mice did not show any pregnancy-associated abnormalities. Conclusions: These observations in the preeclampsia placenta, cultured trophoblasts, and Ttr transgenic mice indicate that TTR aggregation is an important causal contributor to preeclampsia pathophysiology.